2018
DOI: 10.1155/2018/9183053
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming of Capuchin Monkey Adrenal Dysfunction by Gestational Chronodisruption

Abstract: In the capuchin monkey (Cebus apella), a new-world nonhuman primate, maternal exposure to constant light during last third of gestation induces precocious maturation of the fetal adrenal and increased plasma cortisol in the newborn. Here, we further explored the effects of this challenge on the developmental programming of adrenal function in newborn and infant capuchin monkeys. We measured (i) plasma dehydroepiandrosterone sulphate (DHAS) and cortisol response to ACTH in infants with suppressed endogenous ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…As adults, the offspring gestated under chronodisruption, display multiple physiological changes including increased heart rate, blood pressure, body weight, and glucose tolerance, among others (see Table 1). In this context it is important to keep in mind that the effects on the offspring of gestational chronodisruption have been studied experimentally in several species using models, such as maternal pinealectomy, 83,92–94 maternal exposure to constant light 67,78–80,84,85,95 and maternal exposure to chronic phase shifts during gestation, 20,21,23,76,77,96 that display in common the alteration or suppression of the maternal circadian rhythm of melatonin, shifting maternal circadian rhythms of glucose, and suppressing the maternal rhythms of activity, temperature, and heart rate. In these models has been demonstrated that the impairment in fetal organs at circadian and physiological levels are translated to the offspring inducing metabolic impairment, with higher response to intraperitoneal glucose challenge, increasing adrenal response to adrenocorticotropic hormone in vitro, free‐running of corticosterone and permanent effects in plasma melatonin, that remain for the whole life, in which the nocturnal increase of melatonin was absent (Table 1).…”
Section: Long‐term Consequences Of Gestational Chronodisruption On Of...mentioning
confidence: 99%
“…As adults, the offspring gestated under chronodisruption, display multiple physiological changes including increased heart rate, blood pressure, body weight, and glucose tolerance, among others (see Table 1). In this context it is important to keep in mind that the effects on the offspring of gestational chronodisruption have been studied experimentally in several species using models, such as maternal pinealectomy, 83,92–94 maternal exposure to constant light 67,78–80,84,85,95 and maternal exposure to chronic phase shifts during gestation, 20,21,23,76,77,96 that display in common the alteration or suppression of the maternal circadian rhythm of melatonin, shifting maternal circadian rhythms of glucose, and suppressing the maternal rhythms of activity, temperature, and heart rate. In these models has been demonstrated that the impairment in fetal organs at circadian and physiological levels are translated to the offspring inducing metabolic impairment, with higher response to intraperitoneal glucose challenge, increasing adrenal response to adrenocorticotropic hormone in vitro, free‐running of corticosterone and permanent effects in plasma melatonin, that remain for the whole life, in which the nocturnal increase of melatonin was absent (Table 1).…”
Section: Long‐term Consequences Of Gestational Chronodisruption On Of...mentioning
confidence: 99%
“…Answering this question is important for understanding the impact of maternal chronodisruption, which may occur in pregnant women exposed to modern lifestyles, on offspring. It has been found that chronodisruption in utero leads to pathological phenotypes later in adulthood ( Mendez et al, 2016 ; Richter et al, 2018 ; Salazar et al, 2018 ; Varcoe et al, 2018 ) that may not be rescued by quality of maternal care during postnatal period ( Smarr et al, 2017 ). Therefore, temporal organization during fetal development seems to be important for good health in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Different perinatal light paradigms cause 'clock' genes in neurons from the suprachiasmatic nuclei (SCN, the "master" clock in the brain) of rodents to behave differentially in later life (Ciarleglio et al 2011;Tackenberg and McMahon 2018). Later life physiology, in particular metabolic processes, can also be differentially affected by different perinatal light paradigms (Ciarleglio et al 2011; Lewis and Erren 2017a;Mendez et al 2019;Mizutani et al 2017;Ohta et al 2006;Richter et al 2018;Salazar et al 2018). Daylight is the predominant environmental time-cue or 'zeitgeber' for the CTS in humans (Aschoff 1951(Aschoff , 1954Duffy et al 1996).…”
Section: Introductionmentioning
confidence: 99%